The Effectiveness of Discovery Learning with Loose Parts in Increasing Student Interest and Activity in Science Learning - Nur Efendi; Salma Ramadhina Fatahillah; Ira Puspita Sari; Yusuf Irawan (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Problems that often arise are the lack of understanding in implementing innovative learning models, which makes students quickly bored and have difficulty understanding the material. This study aims to analyze the effectiveness of the Discovery Learning learning model with loose parts media in increasing students' interest and activity in science learning. The method in the study used a quantitative approach to quasi-experimental design. Data were collected through observation and documentation. The results of the study showed that the application of Discovery Learning with loose parts media significantly increased students' interest and learning activity in science learning. The use of this method is effective in creating an interesting learning environment, and is able to contribute to improving student learning outcomes. The results of the hypothesis test between the two groups prove that loose parts of the media can affect the ability to understand the Nature of Science and Scientific Methods.